‘Balia – Perayu Amuk Dewata’: Pengobatan Tradisional di Antara Modernitas dan Agama di Masyarakat Kaili - Safrillah - Safrillah (ETNOSIA : Jurnal Etnografi Indonesia, 2017)
Balia is a traditional ritual which is potentially disappeared due to the development of modern health care and the influence of Islam. In fact, balia still exists in this ever changing world. Balia even attracts public attention when it was performed in the main stage of Festival Nomoni in 2016. Balia has become ‘the bridge’ between the history of Kaili and Bugis through Sawerigading. Balia is a symbolic expression of the relationship between human beings and their spiritual nature that was originated from belief system towards god (dewa) and spirit (roh) which control the object of nature. Balia can survive because of its efficacy to cure diseases even though it is economically quite expensive. The efficacy of balia seems to confirm the view that disease is a 'spiritual game', which is identified with idolatry (kemusyrikan). In the face of conflict with the teachings of Islam, Kaili residents use the strategy of 'cultural dialogue' by integrating elements and symbols of Islam in the implementation of the tradition of balia.